42 reasons to hate the universe : (and one reason not to) - Ferrie, Chris; Fairclough, Wade David; LaGinestra, Byrne (Sourcebooks, 2024)
"Yes, the Universe is beautiful. And, despite all our scientific progress, it's still pretty mysterious. But you know what? The Universe is also kind of an asshole. Consider that you are just a group of atoms structured in a specific way that you can try to understand this thing we call existence. Those same atoms could have just as easily been used to make the dog shit you are cleaning off your shoes. The fact is, when you zoom out and look at the Universe and how it functions, you'll see that it's usually not in our favor. Many of the laws of physics are just kind of... dick-ish. In this book, you'll discover why: You're an aging mutant Most water will kill you The Universe could be deleted any second And 39 more reasons to hate the Universe-along with the one reason we have to love it despite all the shit it throws our way"--